2004
DOI: 10.1002/pen.20144
|View full text |Cite
|
Sign up to set email alerts
|

Online measurements of crystallinity using Raman spectroscopy during blown film extrusion of a linear low‐density polyethylene

Abstract: Real-time, Raman spectroscopic measurements of crystallinity during the blown film extrusion of a linear low-density polyethylene (LLDPE) are reported. The take-up ratio (TUR), inflation air pressure, and cooling conditions were varied, and their effect on the development of crystallinity was studied. The results indicate that the crystallization process starts at the freeze line, increases along the film line, and finally plateaus. It was observed that with changing processing conditions, the differences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Raman spectra were quantified for crystallinity values following a protocol that was established in earlier studies. [20,21] Real-time temperature measurements were also performed using an IRCON IR pyrometer (Modline 340, Niles, IL).…”
Section: Process Measurements and Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Raman spectra were quantified for crystallinity values following a protocol that was established in earlier studies. [20,21] Real-time temperature measurements were also performed using an IRCON IR pyrometer (Modline 340, Niles, IL).…”
Section: Process Measurements and Instrumentationmentioning
confidence: 99%
“…Recently, we have reported on the use of real-time Raman spectroscopy to estimate crystallinity development during blown film extrusion of polyolefins. [20,21] Our study established Raman spectroscopy as a robust and nondestructive technique to monitor crystallinity evolution in industrial settings, as it offers remote sampling capabilities when coupled via fiber optics. The integration of real-time experimental results with modeling efforts was reported in a recent study.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated degree of crystallinity of the 1.5, 2.0 and 2.4 mm GMBs obtained from the first melt curve using method-4 were insignificantly different but were slightly less than the calculated degree of crystallinity of 1.0 mm GMB (Figure 14), although the specimens from 1.0, 1.5, 2.0 and 2.4 mm have the same physical characteristic (Table 2, Figure 4). This trend may be: (a) showing the counteracting effects of an increase in crystallisation rates of the thinner GMBs due to the higher stress induced by the higher take-up ratio being opposed by the decrease in crystallisation rates for thinner GMBs because of their higher cooling rates and lesser time for crystallisation and annealing (Cherukupalli and Ogale 2004); or (b) an anomaly resulting from the different movement of the specimens in the DSC (as explained earlier). If explanation (a) is true, then it appears that the effect of the takeup-ratios of 1.5, 2.0 and 2.4 mm GMB was cancelled by the effect of their cooling rates; however, the effect of the higher take-up ratio for the 1.0 mm GMB on crystallisation was slightly higher than the effect of the cooling rates that 1.0 mm GMB experienced during the manufacturing process.…”
Section: Crystallinity Test Resultsmentioning
confidence: 91%
“…Keller and Machin (1967) modified the row-nucleated structure model with respect to the level of stress into two models: (a) Keller/ Machin I: under low stress the lamellae grow radially outward in the form of twisted ribbons and (b) Keller/Machin II: under high stress the lamellae grow laterally outward without twisting and the chain axis ( Figure 3) is preferentially oriented in the machine direction. According to the findings of Sukhadia (1994), Simpson and Harrison (1994), Ghaneh-Fard (1999), Lu et al (2001), Godshall et al (2003), Cherukupalli and Ogale (2004), Zhang et al (2004) and Fatahi et al (2005), the mechanical and physical response of polyethylene films manufactured using the blown film method are a strong function of its morphological structure. For example, Lu et al (2001) studied HDPE blown films and found that the morphological structure of HDPE films was comprised of two superimposed row-nucleated structures.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation